Language Impairment, Motor Delay and Rolandic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at the Epilepsy Center and Department of Neurology, Maastricht University Medical Center, The Netherlands investigated a correlation between language, learning and locomotor impairments in a cohort of 48 children (6.5-13 years of age; 26 boys and 22 girls) with rolandic epilepsy referred to the Epilepsy Center between 2001 and 2009.